Mild and Efficient Cobalt-Catalyzed Cross-Coupling of Aliphatic Amides and Aryl Iodides in Water - Tan, Bryan Yong-Hao; Teo, Yong-Chua (Synlett, 2015)
A convenient protocol for the C–N cross-coupling of aliphatic amides and iodobenzene is demonstrated using a simple and inexpensive Co(C2O4)·2H2O/N,N′-dimethylethylenediamine (DMEDA) catalytic system in water. Good yields of N-arylated products were isolated (up to 85%) and the protocol has been successfully applied to the synthesis of the anticancer drug, flutamide.
Keywords: cobalt; N-arylation; cross-coupling; aliphatic amide; water